Experimental results on the vibratory energy exchanges between a linear system and a chain of nonlinear oscillators. (22nd December 2018) - Lamarque, C.-H.; Savadkoohi, A. Ture; Charlemagne, S.
Abstract: Experimental results on a nonlinear chain coupled to a main system are presented. The chain is composed of eight moving masses, each one possesses local nonlinear restoring forcing function and global linear springs for coupling to other masses. The main system is coupled to the first mass of the chain via a linear spring. The main system is under external sinusoidal excitation with sweeping frequency around its targeted mode. Experimental results show that according to the amplitude of the excitation, the system can reach periodic or modulated regimes. The goal of using the nonlinear chain is to examine experimentally the possibility of localization of the vibratory energy of the main system into the chain for the aim of passive control.